Bioethics and the brain - Glannon, Walter (Oxford University Press, 2007)
All these procedures and drugs alter the neural correlates of our mind and raise fascinating and important ethical questions about their benefits and harms. They are, in a sense, among the most profound bioethical questions we face, since these techniques can touch on the deepest aspects of the human mind: free will; personal identity; the self; and the soul. This is the first single-author book on what has come to be known as neuroethics. Walter Glannon uses a philosophical framework that is fully informed by cutting edge neuroscience as well as contemporary legal cases such as Terri Schiavo, to offer readers an introduction to this fascinating topic